Keanekaragaman Serangga Hama dan Musuh Alami pada Fase Vegetatif Hingga Generatif Tanaman Padi (Oriza Sativa L.) di Desa Jejangkit Muara Kecamatan Jejangkit Kabupaten Barito Kuala - Nasrullah, Moh.; Razie, Fakhrur; Heiriyani, Tuti (Agroekotek View, 2023)
Paddy (Oryza sativa L.) is a food crop that remains a top priority in agricultural development, with the increasing world population and humans starting to face various problems including food supply. The decrease occurred due to the increasingly complex pest problem felt by farmers from year to year, this is thought to be due to global climate change which affects local seasons/weather patterns which are closely related to pest development. This study aims to determine the diversity of insect pests and enemies. naturally in the vegetative to generative (harvesting) phase. This study uses direct observation and assessment methods of insect pests and natural enemies in the field by using light traps to trap insects. The way to find out the number of trapped insects is by using the diversity index, richness index and dominance index. The results of this study indicate that insect pests attack more rice plants, namely 2112 than natural enemies 1728.